Simple gill Smear Staining for Diagnosis of Amoebic Gill Disease - Zilberg, D; Barbara Nowak; Carson, J; Wagner, T (1999)
Amoebic gill disease (AGD) caused by a Paramoeba spp. is the major disease affecting cultured Atlantic salmon in Tasmania. Primary diagnosis of the disease on the farm relies on gross morphology, and it is then confirmed in the laboratory with an immunofluorescence antibody test (IFAT). In this study we evaluated the potential use of a rapid method for the detection of AGD using a Quick Dip* stain and compared it to the established IFAT. Quick Dip* staining revealed 96% agreement with IFAT in the determination whether a sample is positive or negative for AGD, with sensitivity and specificity values of 88.23% and 92.85%, respectively and a kappa value of 0.7628. Mean number of Paramoeba spp. per field of view positively correlated in the two methods (r=0.972), although it was significantly greater when IFAT was used. Quick Dip* stained Paramoeba spp. in a mucus smear is identified by its morphological features. It measures 15 to 20 Î¼m, appearing dark blue with a darker blue and purple-stained internal organelles. The study suggests that Quick Dip* can be used as a fast method for the diagnosis of AGD.